2010
DOI: 10.1007/s11705-009-0300-8
|View full text |Cite
|
Sign up to set email alerts
|

Influences of additives on the crystal habit of potassium chloride

Abstract: By means of constant control speed cooling crystallization, the influences of four additives, including lead chloride, cadmium chloride, sodium salicylate, and quaternary ammonium salt, on the crystal habit of KCl were investigated. The results show that the crystal habit of KCl is cube without additives, the crystal habit of KCl is ellipsoid-like in the presence of Pb 2+ , the crystal habit of KCl is strip in the presence of Cd 2+ , and the crystal habit of KCl is cavate cube in the presence of sodium salicyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
3
0
2
Order By: Relevance
“…On the other hand, the amorphous aggregates correspond to the insoluble fine particles. A similar image is shown in Freyer and Voigt, 22 corresponding to calcium sulfate crystals, while in de Oliveira et al 23 and Guo et al, 24 cubic shapes of sodium chloride and potassium chloride crystals are presented, respectively. Therefore, it can be concluded that the analyzed sample is composed of crystals of CaSO 4 and insoluble particles aggregated to them.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, the amorphous aggregates correspond to the insoluble fine particles. A similar image is shown in Freyer and Voigt, 22 corresponding to calcium sulfate crystals, while in de Oliveira et al 23 and Guo et al, 24 cubic shapes of sodium chloride and potassium chloride crystals are presented, respectively. Therefore, it can be concluded that the analyzed sample is composed of crystals of CaSO 4 and insoluble particles aggregated to them.…”
Section: Discussionsupporting
confidence: 60%
“…There are different factors that influence the morphology, like temperature [2], stirring rate, seed crystal [3], impurities [4], additives, and so on, among which the additives have attracted wide attention because of their simplicity, effectiveness, and low cost [5]. A great number of studies have shown that additives have an influence on the morphology [6][7][8][9][10] or growth rate of crystals. For example, specific additives may change the growth rate of different crystal faces [11].…”
Section: Introductionmentioning
confidence: 99%
“…The KCl is observed to be a good material for optical studies, 27 Agriculture as potassic manure and also a basic potash production in industries. 31 For these reasons a large amount of experimental and theoretical research on structural study of KCl substance has been a major concerned. 19 One of the methods that take serious attentions recently due to its simplicity and accuracy in exploring the crystal and molecular structure of many compound is the computer simulation, based on the quantum mechanical approach using the available computer language or software.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a first-principles study of the vibrational properties of H centers in KCl crystals has been reported. 31 In this work we treat a potassium chloride crystal as a face cubic crystal (FCC) and use a quantum mechanics based on Cartesian linear approch 10 to obtain the dynamical matrices, 20 density of state and specific heat capacity analytically. The FORTRAN simulation code was used to obtain the numerical results.…”
Section: Introductionmentioning
confidence: 99%